THE EFFECT OF ADDING FERMENTED DRAGON FRUIT PEELS JUICE IN DRINKING WATER ON SLAUGHTER WEIGHT AND OFFALS INTERNAL PERCENTAGE OF QUAILS - L. A. A., Kaban; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
The present research aims to determine the effect of adding fermented dragon fruit peels juice to drinking water on the percentage of offals internal japanese quail aged 12-16 weeks. 484 This research was design using Completely Randomized Design (CRD) with 3 treatments and 6 repetitions, which each repetitions consists of 10 quails. The treatments given were drinking water without fermented dragon fruit peels juice (P1), drinking water with 4% fermented dragon fruit peels juice (P2), and drinking water with 6% fermented dragon fruit peels juice (P3). The variables observed were of slaughter weight, percentage of liver, percentage of bile, percentage of heart, and percentage of quail spleen. The results of this research proved the slaughter weight of quail showed higher significantly results (P<0,05) than the control with the highest slaughter weight in drinking water with 6% fermented dragon fruit peels juice (P3). However, the percentage of offals internal (liver, bile, heart, and spleen) showed no significant difference (P>0,05). Based on the results of the research, it can be concluded that giving drinking water to quail (Coturnix coturnix japonica) aged 12-16 weeks with the addition 4% and 6% fermented dragon fruit peels juice can increase slaughter weight with offals internal percentage (liver, bile, heart, and spleen) still within normal limits (standard).